Frequency Distribution of Causes and Severity of Thrombocytopenia in Patients of All Age Groups (Medical Forum Monthly, 2021)
Objective: The present study was planned to see the frequency distribution of causes and severity of thrombocytopenia in thrombocytopenic patients of all the age groups.Study Design: Descriptive cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Pathology, Ayub Medical College Abbottabad from July 2018 to April 2021.Materials and Methods: As much as 120 patients with blood reports showing thrombocytopenia were studied. Their blood counts were repeated with sodium citrate based anticoagulant followed by peripheral blood film examination for platelet clumps aggregates.Results: A total of 120 patients had thrombocytopenia on initial testing. Screening by sodium citrate and blood film method revealed nine patients with pseudo thrombocytopenia. They were excluded from the study. The remaining 111 patients had true thrombocytopenia with 45% male & 55 % female, male to female ratio being 0.82:1. 20 patients aged < 25 years, 70 were 25 - 50 years & 30 were > 50 years old, with mean age 42±12 years.Conclusion: Primary ITP & acute infection was the most frequent cause of thrombocytopenia (2/3rd), followed by acute leukemia and secondary ITP (1/3rd). Mild thrombocytopenia was the most frequent finding (2/3rd), followed by moderate & severe thrombocytopenia (1/3rd each).